WENO schemes on arbitrary mixed-element unstructured meshes in three space dimensions - Tsoutsanis, Panagiotis; Titarev, Vladimir A.; Drikakis, Dimitris (Elsevier, 2010)
The paper extends weighted essentially non-oscillatory (WENO) methods to three dimensional mixed-element unstructured meshes, comprising tetrahedral, hexahedral, prismatic and pyramidal elements. Numerical results illustrate the convergence rates and non-oscillatory properties of the schemes for various smooth and discontinuous solutions test cases and the compressible Euler equations on various types of grids. Schemes of up to fifth order of spatial accuracy are considered.
Keywords: WENO; Unstructured; Tetrahedral; Hexahedral; Prismatic; Pyramidal; Mixed-element; Three space dimensions; Very high order; Euler